FAKTOR YANG MEMPENGARUHI WARGA BELAJAR MEMASUKI PROGRAM KEJAR PAKET C DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) BINA KREASI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Marni, Deska; Maemunaty, Titi; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Research it is based on factor that influences residents learn enter paket C in Pusat Kegiatan Belajar Masyarakat (PKBM) Bina Kreasi Kecamatan Tenayan Raya Kota Pekanbaru seen from residents learn factors PKBM. Factor that influences residents learn enter paket C look at from 9 the basis of implementation in Pusat Kegiatan Belajar Masyarakat (PKBM) Bina Kreasi Kecamatan Tenayan Raya Kota pekanbaru the study group, a source of learning (tutor), learning (the public, management, implementing ), of learning tools, place learning, pogram learning, yeast learning, funds learning and study results. The formulation the research is how high factors affect people learn entering paket C in Pusat Kegiatan Belajar Masyarakat (PKBM) Bina Kreasi Kecamatan Tenayan Raya Kota Pekanbaru?. The purpose of this research is to know the level of factors affect residents learn enter paket c in Pusat Kegiatan Belajar Masyarakat (PKBM) Bina Kreasi Kecamatan Tenayan Raya Kota Pekanbaru. Population in this study as many as 35 people .Then the researcher take altogether for the study sample 35 people for research in Bina Kreasi and 20 people to the trial elsewhere by using saturated techniques of sampling. An instrument data collection namely poll with 65 a statement and if the trial live 60 a statement that valid to make instrument in research. Through data analysis of the quantitative descriptive analysis. So, a conclusion can be drawn , factor that influences residents learn enter paket c in Pusat Kegiatan Belajar Masyarakat (PKBM) Bina Kreasi Kecamatan Tenayan Raya Kota Pekanbaru within high.Key words: Factor, Factor That Influences Residents Learn